22nd International Conference on Human-Computer Interaction With Mobile Devices and Services 2020
DOI: 10.1145/3379503.3403551
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Effect of Audio Degradation on Privacy Perception And Inference Performance in Audio-Based Human Activity Recognition

Abstract: Audio has been increasingly adopted as a sensing modality in a variety of human-centered mobile applications and in smart assistants in the home. Although acoustic features can capture complex semantic information about human activities and context, continuous audio recording often poses significant privacy concerns. An intuitive way to reduce privacy concerns is to degrade audio quality such that speech and other relevant acoustic markers become unintelligible, but this often comes at the cost of activity rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…[22]. Expanding on previous work in the area of audio scrambling [13], we suggest increased research to explore adversarial AI components that check whether speech content and individual identity could be reconstructed from degraded or scrambled audio. The purpose of the adversarial component (which we have defined as system A) is to enhance the trust partnership between AI and consumers.…”
Section: Research Directions and Challenges 31 Reliability: Data Degr...mentioning
confidence: 97%
See 1 more Smart Citation
“…[22]. Expanding on previous work in the area of audio scrambling [13], we suggest increased research to explore adversarial AI components that check whether speech content and individual identity could be reconstructed from degraded or scrambled audio. The purpose of the adversarial component (which we have defined as system A) is to enhance the trust partnership between AI and consumers.…”
Section: Research Directions and Challenges 31 Reliability: Data Degr...mentioning
confidence: 97%
“…Many people have a reasonable expectation of privacy when it comes to how their smart technologies store, process, and transmit audio data [5]. Recent work in audio-based activity recognition has shown that people begin to trust audio privacy more if monitored speech has been rendered unintelligible to humans through an audio degradation technique called scrambling [13]. Some types of scrambling or noise may make audio content unintelligible to humans, but does not neutralise information in the audio signal for an AI system.…”
Section: Research Directions and Challenges 31 Reliability: Data Degr...mentioning
confidence: 99%
“…However, this solution is primarily designed for text data and is not directly applicable to preserve privacy for daily conversations. Liang et al [18] study the users' perception in an environment in which the audio is recorded continuously. The authors propose that users' privacy perception improves if the quality of the audio is degraded before it is recorded.…”
Section: Media Richness Theorymentioning
confidence: 99%
“…Speech augmentation threatens this paradigm by recording and transmitting information over digital means. Yet, few studies consider privacy in face-to-face conversations, and most of the proposed solutions reduce speech intelligibility [4,10,18,20,29].…”
Section: Introductionmentioning
confidence: 99%
“…Transferring knowledge from a source domain to a target task can be a useful way to enrich the learning of the target dataset [7]. It is particularly meaningful in real-world audio analysis where the target audio accessibility can be limited due to challenges such as scalability [17] and privacy constraints [18]. For acoustic classification, transfer learning has been successfully applied both across tasks [19,20,21,22,23] and across modalities [5,24].…”
Section: Related Workmentioning
confidence: 99%